O percurso da punição e o desafio ressocializador: o projeto reeducar - Hoaegen, Nina Cruz Antony (2019)
The crisis installed in the prison system reflects the institutional tension prevailing in the country, especially in the field of public security. In a scenario in which the increasing increase in incarceration rates is not able to contain urban violence, the search for an exit corresponds to all instances of public power acting in the path of socialization and prevention, increasing the responsibility of the Power Judiciary to offer inclusion mechanisms, several of orthodox models that interpret prevention as a mere purpose of the penalty, in a dissuasive. Materials and methods: In order to achieve this work, we used the deductive method in the historical and descriptive section and inductive method for the data collection of the REEDUCAR Project, with bibliographic, documentary and quantitative research. The REEDUCAR data were extracted from several spreadsheets directly provided by the Project team, using the tool of the Court of Justice of the Amazon, Justice Automation System (e-SaJ) for a nominal search for the reiterators. Objectives: In this context it is discussed whether the Reeducar project, an initiative of the Amazonas Court of Justice, is capable of fulfilling this socializing purpose, being instrumented from mechanisms that guarantee the reach of the citizenship to the provisional prisoners and the access to means that make possible their social inclusion, preventing a repetition of crime. Results: As for the historical part, there was an evolutionary nonlinearity in the context of humanization of sentences. With regard to the research about the criminal repetition of the people served by the project, in a universe of 237 individuals, only 37 people returned to commit crime (15.6% of the total). Conclusions: There are difficulties that are found both in the context of investments in the creation of public policies involving supposed delinquents, and in the risks of authoritarianism in social control by the State when involving Ressocialização. However, the Reeducar Project representing an unprecedented initiative as a court effort brings good indications in combating the dehumanization of individuals considered marginalized.